Time to blastulation is superior to individual components of embryo grading for live-birth prediction - Sarah M. Moustafa, M.D; Emma M. Rosen, M.S.P.H; Caitlin Boylan, B.S; Jennifer E. Mersereau, M.D., M.S.C.I (Elsevier, 2020)
Objective: To compare components of the embryo grading system with time for blastocyst formation (i.e., day of embryo transfer) for predicting live-birth rate in frozen embryo transfer cycles. Design: Retrospective cohort study. Setting: University-affiliated fertility clinic. Patient(s): From January 2015 to October 2018, 870 frozen embryos transferred in a total of 509 women and 728 cycles at our institution. Intervention(s): None. Main Outcome Measure(s): Probability of live birth per cycle. Result(s): In unadjusted analysis of embryo grading components, both inner cell mass (ICM) and trophectoderm grades demonstrated a correlation with live-birth rates. However, this effect was lost in the ICM subgroup analysis by day of embryo transfer and preserved only in declining trophectoderm grades of day-6 transfers. In the adjusted analysis for prediction of live birth, only day of transfer was statistically significant. When assessing the composite score by Society for Assisted Reproductive Technology (SART) embryo grading, good embryos that blastulated on day 6 were statistically significantly less likely than day-5 embryos to result in live birth (risk ratio 0.70; 95% confidence interval, 0.58-0.85). Finally, in a predictive model adjusted for all individual components of embryo grade, the day of blastulation was the only statistically significant contributor. Conclusion(s): Time to blastulation is superior to other individual components of embryonic grading for prediction of live birth.